IL-23 tunes inflammatory functions of human mucosal-associated invariant T cells - Laetitia Camard; Tharshana Stephen; Hanane Yahia-Cherbal; Vincent Guillemot; Sébastien Mella; Victoire Baillet; Hélène Lopez-Maestre; Daniele Capocefalo; Laura Cantini; Claire Leloup; Julie Marsande; Katherine Garro; et al. (iScience, 2025)
Summary: IL-23 signaling plays a key role in the pathogenesis of chronic inflammatory and infectious diseases, yet the cellular targets and signaling pathways affected by this cytokine remain poorly understood. We show that IL-23 receptors are expressed on the large majority of human mucosal-associated invariant T (MAIT), but not of conventional T cells. Protein and transcriptional profiling at the population and single cell level demonstrates that stimulation with IL-23 or the structurally related cytokine IL-12 drives distinct functional profiles, revealing a high level of plasticity of MAIT cells. IL-23, in particular, affects key molecules and pathways related to autoimmunity and cytotoxic functions. Integrated analysis of transcriptomes and chromatin accessibility, supported by CRISPR-Cas9 mediated deletion, shows that AP-1 transcription factors constitute a key regulatory node of the IL-23 pathway in MAIT cells. In conclusion, our findings indicate that MAIT cells are key mediators of IL-23 functions in immunity to infections and chronic inflammatory diseases.